Réponses

2014-04-27T18:45:49+02:00
E = (2x+3) (5-x)
e =10x -2x²+15-3x
e = -2x² +7x +15

f = (1-3x)(2x-1) +3x(1-4x)
f = 2x -1 -6x² +3x +3x-12x²
f = -18x² +8x -1

si x = -2
alors
e = -2 (-2)² +7 (-2) +15
e = -2(4) -14 +15
e = -8 -14 +15
e = -7

f = -18 (-2)² +8(-2) -1
f =  -72 -16-1
f = -89

si x = 5

e = -2x² +7x +15
e = -2 (5)² + 7(5) +15
e = -50 +35 +15
e = 0

f = -18x² +8x -1
f =  -18 (5)² +8(5) -1
f = -18 (25)+40 -1
f = - 450 +39
f = - 411

si x = 1/2

e = -2x² +7x +15
e = -2 (1/2)² + 7(1/2) +15
e = -2 ( 1/4) +7/12 +15
e = -2/4 +7/12 +15
e = -6/12 +7/12+ 180/12
e = 181/12

f = -18x² +8x -1
f= -18 (1/2)² +8(1/2) -1
f=  -18 (1/4) +8/12 -1
f = -18/ 4 + 8/12 -1
f = - 54/12 +8/12 -12/12
f =  -58/12
f = -29/6